Natural resources and environment in Cam Ranh bay and sustainable development orientation - Quy, Tran Dang; Duong, Nguyen Thuy; Ngoc, Nguyen Thi; Nhuan, Mai Trong (VNU Journal of Science: Earth and Environmental Sciences; Vol 25 No 3, 2009)
Abstract